Long-term degradation study of Polytetrafluoroethylene in a low temperature oxygen plasma - Wagner, Tobias; Rohnke, Marcus; Janek, Jürgen; Justus Liebig University Giessen (My University, 2024)
Atomic oxygen (AO) is the most common gas species in the Low-Earth-Orbit (LEO) and responsible for material degradation of the outer shell of spacecrafts within this space region. Due to their similar properties, low temperature oxygen plasmas are suited for material degradation studies taking place on earth instead of quite expensive space studies. Here we focus on the long-term degradation of Polytetrafluoroethylene (PTFE), which is often employed on the outside of spacecrafts. Up to date, there is no complete understanding of the degradation process on molecular level, which is necessary for materials improvement and new materials development. For the degradation studies, a self-constructed capacitively driven 13.56 MHz RF reactor was used to generate an oxygen plasma for the simulation of LEO conditions. PTFE was characterised in the pristine state and after AO treatment at different times by ToF-SIMS, XPS and SEM. During plasma treatment, the samples show a linear mass loss behaviour. ToF-SIMS surface analysis reveal mass fragments which show a clear chemical reaction of oxygen species with PTFE. The presence of these molecular indicators was verified by XPS, where additional carbon species were found after plasma treatment. SEM micrographs showed an inhomogeneous degradation on the surface in the first hours similar to actual LEO exposure. For a complete understanding of the degradation progress, operando mass spectrometric studies of the plasma composition were carried out to detect volatile degradation products. In summary, a steady degradation has been observed that leads to constant mass loss, defluorination, chain shortening and insertion of oxygen into the polymer.
Keywords: ddc:540